2019
DOI: 10.1021/acsami.9b18784
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Fullerene/Porphyrin Cocrystals: Near-Infrared Light Sensing through Component Interactions

Abstract: Recently, organic donor−acceptor (D−A) cocrystals have attracted special interest as functional materials because of their unique chemical and physical properties that are not exhibited by simple mixtures of their components. Herein, we report the preparation of one-dimensional novel D−A cocrystals from C 60 and 5,10,15,20-tetrakis(3,5-dimethoxyphenyl)porphyrin (3,5-TPP); these cocrystals have near-infrared (NIR) light-sensing abilities, despite each of their component molecule individually having no NIR light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
0
23
1
Order By: Relevance
“…The presence of the porphyrin center metal ion was believed to play a crucial role in the strong D‐A interaction with C 60 and greatly reduce the π–π stacking distance between porphyrin and C 60 . Moreover, the C 60 /3,5‐TPP micrometer‐sized co‐crystals, prepared through a liquid–liquid interfacial precipitation method, revealed n‐type transport characteristic with NIR light‐sensing properties, which were achieved by CT forces and/or π–π interactions in the ground state [85] . A new black co‐crystal based on La@C 82 and [NiII (OEP)] was obtained by solution diffusion method with the highest electron mobility up to 0.9 cm 2 V −1 s −1 , measured by fast flash solution time‐resolved microwave conductivity (TRMC) measurement [86] …”
Section: Functionality Investigation Of Charge‐ Transfer Complexesmentioning
confidence: 99%
“…The presence of the porphyrin center metal ion was believed to play a crucial role in the strong D‐A interaction with C 60 and greatly reduce the π–π stacking distance between porphyrin and C 60 . Moreover, the C 60 /3,5‐TPP micrometer‐sized co‐crystals, prepared through a liquid–liquid interfacial precipitation method, revealed n‐type transport characteristic with NIR light‐sensing properties, which were achieved by CT forces and/or π–π interactions in the ground state [85] . A new black co‐crystal based on La@C 82 and [NiII (OEP)] was obtained by solution diffusion method with the highest electron mobility up to 0.9 cm 2 V −1 s −1 , measured by fast flash solution time‐resolved microwave conductivity (TRMC) measurement [86] …”
Section: Functionality Investigation Of Charge‐ Transfer Complexesmentioning
confidence: 99%
“…The increasing current at 810 nm was attributed to the CT state in the C 60 /3,5-TPP cocrystals were excited to generate excitons that subsequently separated. Due to the CT absorption band and component bands, the phototransistor based on the C 60 /3,5-TPP cocrystal exhibited a strong photoresponse at 660 nm, and the measured photosensitivity was 4.5 (0.05 mW/cm 2 ) ( Figure 6D ) ( Wakahara et al, 2020 ).…”
Section: Electronic Properties and Functionalitiesmentioning
confidence: 99%
“…(C) Wavelength dependence of the output characteristics of a C 60 /3,5-TPP phototransistor at V G = 80 V when illuminated with different LEDs (E ligh t = 0.1 mW/cm 2 ). (D) Output characteristic curves of the phototransistor based on C 60 /3,5-TPP at V G = 80 V when illuminated with 660 nm light of different intensities (E light ) (Reproduced from Wakahara et al (2020) with permission from American Chemical Society, Copyright 2020.).…”
Section: Electronic Properties and Functionalitiesmentioning
confidence: 99%
“…6 Following these earlier studies, various FETs based on D-A cocrystals were reported. [7][8][9][10][11] There are many reports on ambipolar FETs based on novel organic semiconductors, however, the preparation of these semiconductors usually requires complex organic syntheses. One of the advantages of the cocrystallization process, which can be conducted by simply mixing two (or more) molecules together, is the possibility to avoid such complex synthesis pathways.…”
Section: Introductionmentioning
confidence: 99%